(untitled) (Research, Society and Development, 2022)
Introduction: Apheresis is a procedure where blood from a single donor is withdrawn, separated into red blood cells, plasma and platelets. Plateletpheresis is important in the transfusion therapy of cancer patients, reducing the chances of transfusion-related diseases and transfusion reactions. Objective: To present a comparative analysis of the apheresis collection procedures of a hemotherapy service between the years 2017 and 2018, the initial period of its implementation. Methods: 162 apheresis protocols from the blood collection sector of the Transfusion Unit of the University Hospital were used in this study. This is a retrospective, observational study, with a review of data from apheresis donation procedures. Results: 62 apheresis procedures were performed, totaling 200 blood components during the research period. The highest incidence of donors was male (93%) compared to female (7%). We identified 49 cases of adverse reactions to donation (30.2%), the most frequent being: hematoma at the puncture site (40.81%) and lip tingling (38.78%), followed by vasovagal reaction ( 16.33%). Conclusion: The implementation of platelet collection by apheresis in the hemotherapy service promoted greater support for the care of patients with high transfusion needs, agility and improvement in the quality of the blood component offered.